The effect of protest votes on the estimates of willingness to pay for use values of recreational sites - Elisabetta Strazzera; Margarita Genius; Riccardo Scarpa; George Hutchinson (Fondazione Eni Enrico Mattei (FEEM), 2001)
Selectivity bias caused by protest responses in Contingent Valuation studies can be detected and corrected by means of sample selection models. This paper compares two methods: the Heckman 2-steps method and the full ML, applied to data on forest recreation - where WTP is elicited as a continuous variable. Either method has its own drawback: computational complexity for the ML method, susceptibility to collinearity problems for the 2-steps method. The latter problem is observed in our best fitting specification, with the ML estimator outperforming the 2-steps. In this application, overlooking the effect of protest responses would cause an upwards bias of the final estimates of WTP.
Keywords: C35; C51; C81; D60; H41; Q26; 330; Contingent valuation; protest responses; sample selection; MLE; two-steps method; Willingness to pay; Tourismusregion; Bias; Theorie; Schottland; Statistisches Auswahlverfahren; Maximum-Likelihood-Methode